Lyrics by Marina Tsvetayeva in Latvian Translations - Барышникова, Татьяна (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
This article traces back the history of the reception of the works by M. Tsvetajeva in Latvia. Also explores the problem of literary translation of Marina Tsvetayeva’s Lyrics. The analysis of the poems proves that significant attention is dedicated to preserving of those phonetic, syntactic and rhythmical peculiarities of the source texts, which precisely express the expressivity of M. Tsvetayeva’s lyrics. The cases of substantial digression from the source text are reasonably rare and based on the translator’s intension to substitute the author-created neologisms and the words, which do not have equivalents in the Latvian language.